Diet and exercise in the management of obstructive sleep apnoea and cardiovascular disease risk. (28th June 2017) - Dobrosielski, Devon A.; Papandreou, Christopher; Patil, Susheel P.; Salas-Salvadó, Jordi
Obstructive sleep apnoea (OSA) is associated with increased cardiovascular disease (CVD) morbidity and mortality. It is accepted that OSA and obesity commonly coexist. The American Academy of Sleep Medicine recommends dietary-induced weight loss and exercise as lifestyle treatment options for OSA. However, most clinical trials upon which this recommendation is based have focused on establishing the effectiveness of calorie-restricted, often low-fat diets for improving OSA severity, whereas less attention has been given to the means through which weight loss is achieved ( e.g. altered dietary quality) or whether diet or exercise mediates the associations between reduced weight, improved OSA severity and the CVD substrate. The current evidence suggests that the benefits of a low-carbohydrate or Mediterranean diet in overweight and obese individuals go beyond the recognised benefits of weight reduction. In addition, exercise has an independent protective effect on vascular health, which may counter the increased oxidative stress, inflammation and sympathetic activation that occur in OSA patients. This review aims to expand our understanding of the effects of diet and exercise on OSA and associated CVD complications, and sets the stage for continued research designed to explore optimal lifestyle strategies for reducing the CVD burden in OSA patients. This review aims to expand our understanding of the effects of lifestyle interventions in sleep apnoea patients http://ow.ly/HvlK30bsngt